Accelerated method for solving grid equations II (3 – D case) - A, Dang Quang (Journal of Computer Science and Cybernetics, 2016)
In this paper following the parametric extrapolation technique [1] we consider the case when the starting operator is split into the sum of three operators. A result on estimating iteration numbers needed for solving the perturbed problem is obtained. Finally, the advantage of our method over the direct use of the alternating directions method is shown on examples.